EDUKASI PEMILAHAN SAMPAH ORGANIK DAN ANORGANIK PADA ANAK-ANAK KB-RA MASJID JENDERAL SUDIRMAN SURABAYA - Rosalina, Amanda; Sholihah, Mar’atus; Sari, Nur Fajar Aprilia; Gastriani, Ovi Prina; Rismawati, Ria; Fajardini, Ridhani Anita (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Efforts to conserve the environment must begin with small, tangible actions in one's immediate surroundings. Waste management is particularly critical, as every human activity has the potential to generate waste. Therefore, it is crucial to educate young children about the environmental impacts of waste to cultivate their awareness and concern for their environment. This community service initiative aims to enhance early childhood awareness of waste management's importance at KB-RA Masjid Jenderal Sudirman Surabaya through a comprehensive waste sorting program for organic and inorganic materials. The methodology employs a participatory approach, actively engaging children in learning activities. Evaluation involves conducting pre-tests and post-tests, which include giving children different kinds of organic and inorganic waste samples and assessing them to sort the waste into appropriate bins. Data is processed and analyzed using the paired sample T-test approach with Minitab software. The study's results indicate a significant increase in knowledge following educational sessions and assistance in sorting organic and inorganic waste. It is anticipated that this positive behavior will extend to their homes and communities, making waste sorting a concrete step towards mitigating environmental issues caused by waste